2011
DOI: 10.1080/07448481.2010.510163
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress, Energy Drink Consumption, and Academic Performance Among College Students

Abstract: Results confirm gender differences in energy drink consumption and illuminate a need for education regarding use of energy drinks in response to perceived stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
105
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 16 publications
14
105
1
7
Order By: Relevance
“…, 남학생이 [10][11][12][13], 도시에 거주하는 청소년이 [12], 학업성취도가 낮을수록 [10], 가족의 경제적 수준이 낮을 수록 [10,12] 에너지 음료를 많이 섭취했다. (2) 정서적 특성으 로 우울 [11,13], 스트레스와 [7,10] 에너지 음료 섭취 수준 간 정 적 상관관계가 있었다.…”
unclassified
See 1 more Smart Citation
“…, 남학생이 [10][11][12][13], 도시에 거주하는 청소년이 [12], 학업성취도가 낮을수록 [10], 가족의 경제적 수준이 낮을 수록 [10,12] 에너지 음료를 많이 섭취했다. (2) 정서적 특성으 로 우울 [11,13], 스트레스와 [7,10] 에너지 음료 섭취 수준 간 정 적 상관관계가 있었다.…”
unclassified
“…(2) 정서적 특성으 로 우울 [11,13], 스트레스와 [7,10] 에너지 음료 섭취 수준 간 정 적 상관관계가 있었다. 건강 관련 행위 특성으로는 신체활동 수준이 낮을수록 [14,15] 또는 높을수록 [16], 스크린 기반 좌식 활동 수준이 높을수록 [14], 흡연과 [1,11,13] 음주를 [1,11,13] 하는 청소년이, 탄산음료 또는 단 음료를 섭취하는 청소년이 [11,12], 하루 수면시간이 짧고 [1] …”
unclassified
“…Excessive caffeine provides a blast of energy enabling the person to feel good initially but when energy is burned up in 30-40 minutes there is sugar crash [16] . The energizing effects were strongest 30-60 minutes after consumption and were sustained for at least 90 minutes [10] . This explains that majority of participants reported effects immediately and before 12 hours.…”
Section: Frequency and Pattern Of Caffeinated Energy Drink Consumptionmentioning
confidence: 89%
“…It has been reported that the consumption of energy drinks especially among young adults between 18-25 years is currently of great concern as they contain three times the amount present in soft drinks [10] . Personality factors determine the competitiveness of an individual and vigor to achieve success is more predominant in males [10] . This could be the possible reason for consuming energy drinks more often and in higher quantities in males than in females [5] .…”
Section: Socio Demographic Variablesmentioning
confidence: 99%
“…Ukwayi et al's (2013) Nigerian study reported a significant relationship between alcohol use and academic performance such that a unit increase in alcohol consumption would result in 61% decrease in examination success. Pettit et al (2011) also reported that more consumption of energy drink -drink that may have alcohol together with caffeine and other active ingredients in its content -was significantly negatively correlated with undergraduate GPA, suggesting that increased consumption is associated with a fall in the GPA. Although students give several reasons for taking alcohol, including to keep awake and for fun (Ukwayi et al, 2013), perhaps alcoholic drinks negatively affect the GPA by disrupting studies, reducing amount of study time, class attendance, and concentration during examination.…”
Section: Literature Reviewmentioning
confidence: 95%